Seminar dan Pelatihan Pembuatan Media Tanam Cocoblock bersama PKK Desa Kawedusan Kabupaten Kebumen - Fatmawati, Nurlaila; Barokah, Umi; Aprilia, Rennanti Lunnadiyah; Rahmawati, Aulia; Nugroho, Rahmat Joko; Pitaloka, Dicka Galuh; Hidayat, Taufik (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
The community service program consists of seminars and training sessions on the production of cocoblock planting media for the PKK (Family Welfare Movement) of Kawedusan Village, Kebumen Regency. This initiative aims to enhance the knowledge and skills of housewives in utilizing backyard land productively and sustainably. The program is driven by the low level of public understanding regarding alternative planting media and the high potential of coconut husk waste that remains underutilized. The training was conducted using a participatory action learning approach, emphasizing active participant involvement through interactive lectures, discussions, demonstrations, and hands-on practice in making cocoblock. The results of the activity showed a significant increase in participants' understanding, as evidenced by the comparison of pre-test and post-test results, as well as their skills in independently creating cocoblock planting media. Participant engagement was very high, evident from their enthusiasm during practical sessions and willingness to replicate the training outcomes at their respective homes. The program outputs include training modules, tutorial videos, and cocoblock prototypes that can serve as references for developing similar programs. This program has implications for improving household food security, reducing organic waste, and providing opportunities for economic empowerment based on backyard farming. The results of this activity are the application of simple but effective technologies that have a broad impact when implemented in a participatory and sustainable manner